Making projects work effective stakeholder and communication management - Bourne, Lynda (Best practices and advances in program management series, 2015)
This book provides a framework for understanding and managing the factors required for achieving successful project and program outcomes. It presents guidelines to help readers develop an understanding of governance and its connection to strategy as the starting point for deciding what work needs to be done; introduces the idea of an organization's communication ecosystem where information flows freely within and among all organizational layers; explores the importance of the relationships with the project's stakeholder community as keys to project success; describes the theoretical underpinnings of leadership; provides detailed analysis of the different types of project stakeholders; supplies guidance on developing the appropriate messages to meet project and stakeholder needs